Diagnosis by computed tomography of the intervertebral disc extrusion in a geriatric patient: Case report - Nascimento de Carvalho Almeida, Jessyka; Tavares Brito de Medeiros, Tiago; da Nóbrega Carreiro, Artur; Mauro da Cunha, Edson; Vitória Fernandes de Araújo, Débora; Muniz Rodrigues Falcão, Brunna; Yasha Ferreira de La Salles, Ana; José Ayres de Menezes, Danilo (Pubvet, 2018)
Intervertebral disc disease (IVDD) is the most common cause of spinal cord compression in dogs, resulting in neurological problems, which can be classified into two types: Hansen type I (disc extrusion) and Hansen type II (disc protrusion), pressing the nerves of the marrow causing pain, ataxia, paralysis and paraplegia. The indicated treatment should be based on the degree of injury, and may be the clinical treatment associated with physical therapy, for less severe cases, based on the successes in the recovery of the condition, reported in the literature. The objective of this study was to report the efficiency of computed tomography as a complementary tool for conclusive diagnosis of DDIV and the success of clinical and physiotherapeutic treatment for this disease. The animal in question was an 11-year-old poodle that presented ataxia and motor incoordination and was diagnosed with an intervertebral disc extrusion between the T12 and T13 vertebrae by means of computed tomography. The treatment chosen was based on anti-inflammatories and physiotherapy focusing on the strengthening of the epaxial and hipaxial musculature. After 45 days of initiation of treatment, a significant improvement of the animal was observed, however, a future surgical intervention was not ruled out.